A longitudinal examination of thriving in sport performers - Brown, D. J.; Arnold, R.; Standage, M.; Fletcher, D. (Psychology of Sport and Exercise, 2021)
To sustain success in sport, athletes need to function effectively in their competitive encounters and maintain this level over repeated events. Yet, to date, little is known about how athletes can continue to fully function (i.e., thrive) in their sporting encounters. Equally, there is a lack of research in relation to the factors that predict thriving. Testing the premise that basic psychological needs (i.e., for autonomy, competence, and relatedness) predict optimal functioning, the aim of this study was to provide the first longitudinal examination of thriving in sport. Sport performers (N = 268) completed questionnaires assessing thriving and basic psychological need satisfaction on three occasions across 28 days. Longitudinal structural equation modeling showed thriving to be highly predicted by both the experience of recent thriving and the perceived satisfaction of basic psychological needs. These findings highlight an important mechanism through which coaches and practitioners can initiate and maintain thriving in the athletes that they work with across a series of sporting encounters.